Morphological adaptation of adjectival borrowings in modern Lithuanian - Pakerys, Jurgis (Baltistica, 2016)
This paper discusses morphological adaptation of borrowed adjectives in modern Lithuanian. Five types of adaptation are identified: zero adaptation, assignment to inflection class (IC), addition of the derivational suffix, substitution of the derivational suffix, and truncation of the derivational suffix. It is shown that the selection of ICs for borrowings is determined by the register (standard vs. non-standard) and the source language (English vs. non-English), while the choice of adaptational suffixes is determined by their derivational productivity and semantic interpretation of the use of the borrowing.